Concordance of HER2-low scoring in breast carcinomas among pathologists - Snježana Tomić; Tatjana Kapicl Ivković; Marija Milković Periša; Duško Đunđerović; Maja Jovičić Milentijević; Svetlana Oprić; Slobodanka Mitrović; Irena Jovanić; Savelina Popovska; Svitlana Bachurska; Desislava Tashkova; Kalin Kalchev; et al. (Scientific Reports)
Abstract The results from DESTINY-Breast 04 and the subsequent introduction of trastuzumab-deruxtecan as a potential treatement for HER2-low breast cancer necessitated the reevaluation of HER2 scoring. The discordance in HER2 scoring reported in previous studies led us to initiate a regional ring study and to assess our data. This ring study involved 61 breast pathology experts from four countries across the Balkans region. The research comprised 20 samples, including biopsies and surgical specimens, sourced from the archives of one institution. We amassed a total of 1220 scores. The findings indicate a significant degree of interobserver agreement among pathologists in scoring individual categories (scores 0, 1+, 2+, and 3+), with even higher agreement observed when scores 1 + and 2 + were combined into a single, HER2-low category. The findings of this study indicate that adequate education, awareness regarding the therapeutic significance of the HER2-low category, and expertise in breast pathology facilitate the accurate identification of HER2-low breast cancers. These findings will promote ongoing training in breast pathology within the region and will provide a reference for subsequent research efforts.